Jan Chryzostom objaśnia "Hymn o miłości" [1Kor 13] (In I Epistolam ad Corinthios hom. 33-34) - Iluk, Jan (Vox Patrum, 2008)
In 1CorHom, edited in the autumn and winter of 392 and 393 AD, John Chrysostom found a natural opportunity to return to his numerous utterances on the role of love in the lives of people. Obviously, the opportunity was the 13“ chapter of this Letter - The Song of Love. Among his works, we will find a few more smali works which were created with the intention of outlining the Christian ideał of love. Many of the contemporary monographs which were devoted to the ancient understanding of Christian „love” have the phrase „Eros and Agape” in their titles. In contemporary languages, this arrangement extends between sex and love. Both in the times of the Church Fathers (the 4th century AD) and currently, the distance between sex and love is measured by feelings, States and actions which are morę or less refined and noble. The awareness of the existence of many stops over this distance leads to the conviction that our lives are a search for the road to Agape. As many people are looking not so much for a shortcut but for a shorter route, John Chrysostom, like other Church Fathers, declared: the shortest route, because it is the most appropriate for this aim, is to live according to the Christian virtues that have been accumulated by the Christian politeia. There are to be found the fewest torments and disenchantments, although there are sacrifices. Evangelical politeia, the chosen and those who have been brought there will find love) - as a State of existence. In the earthly dimension, however, love appears as a causative force only in the circle of the Christian politeia. Obviously, just as in the heavenly politeia, the Christian politeia on earth is an open circle for everyone. As Chrysostom’s listeners and readers were not only Christians (in the multi-cultural East of the Roman Empire), and as the background of the principles presented in the homilies was the everyday life and customs of the Romans of the time, the ideał - dyam] - was placed by him in the context of diverse imperfections in the rangę and form of the feelings exhibited, which up to this day we still also cali love. It is true that love has morę than one name. By introducing the motif of love - into deliberations on the subject of the Christian politeia, John Chrysostom finds and indicates to the faithful the central force that shaped the ancient Church. This motif fills in the vision of the Heavenly Kingdom, explains to Christians the sense of life that is appropriate to them in the Roman community and explains the principles of organised life within the boundaries of the Church. It can come as no surprise that the result of such a narrative was Chrysostonfs conviction that love is „rationed”: Jews, pagans, Hellenes and heretics were deprived of it. In Chrysostonfs imagination, the Christian politeia has an earthly and a heavenly dimension. In the heavenly politeia, also called by him Chrisfs, the Lord’s or the